2021
DOI: 10.1155/2021/8757996
|View full text |Cite
|
Sign up to set email alerts
|

Association between Diabetes Complications and the Triglyceride-Glucose Index in Hospitalized Patients with Type 2 Diabetes

Abstract: Background. Triglyceride-glucose (TyG) index is a convenient indicator of insulin resistance. It has been shown to be associated with macrovascular and microvascular complications in nonhospitalized diabetic patients. However, whether TyG index is a risk factor of diabetes vascular complications in hospitalized type 2 diabetic patients is unclear. We sought to explore the association between TyG index and the risk of macrovascular and microvascular complications in a large Chinese cohort of hospitalized patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 14 publications
2
44
0
Order By: Relevance
“…Consequently, it is not unexpected to observe the systemic lipid disturbances covering the elevated total cholesterol, triglycerides, low-density lipoprotein cholesterol levels, and apolipoproteins in the present study that in turn evoke the oxidative stress and in ammation, with the potential to elicit lipotoxic cardiomyopathy [32]. These pathologies further support the triggering role of insulin resistance for early initiation of the myocardial function changes in diabetic patients, such as hyperglycemia and dysfunction of lipid oxidation and utilization [33].…”
Section: Discussionsupporting
confidence: 66%
“…Consequently, it is not unexpected to observe the systemic lipid disturbances covering the elevated total cholesterol, triglycerides, low-density lipoprotein cholesterol levels, and apolipoproteins in the present study that in turn evoke the oxidative stress and in ammation, with the potential to elicit lipotoxic cardiomyopathy [32]. These pathologies further support the triggering role of insulin resistance for early initiation of the myocardial function changes in diabetic patients, such as hyperglycemia and dysfunction of lipid oxidation and utilization [33].…”
Section: Discussionsupporting
confidence: 66%
“…The TyG index, derived from FBG and TG, was proven to be a reliable and simple surrogate for metabolic syndrome and IR (22). Mounting evidence has proved the crucial value of TyG index in predicting diabetic complications in patients with T2DM (23)(24)(25). Study by Liu et al showed a significant association between TyG index and the risk of diabetic nephropathy in 682 adult patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…The TyG index, derived from FBG and TG, was proven to be a reliable and simple surrogate for metabolic syndrome and IR [18]. Mounting evidence has proved the crucial value of TyG index in predicting diabetic complications in patients with T2DM [19][20][21]. Study by Liu et al showed a signi cant association between TyG index and the risk of diabetic nephropathy in 682 adult patients with T2DM [22].…”
Section: Discussionmentioning
confidence: 99%